Motivasi Prososial dalam Konteks Komunitas dan Pendidikan: Sebuah Literature Review - Sari, Indah Purnama; Neviyarni, Neviyarni (Lembaga Yasin AlSys, 2025)
Prosocial behavior is a critical foundation for fostering harmonious social relationships, particularly within community settings and educational institutions. Acts such as sharing, helping, and providing emotional support reflect underlying psychological drives and social values shaped through the process of socialization. This study examines prosocial motivation through the lens of contemporary social psychology literature. The review identifies key factors influencing prosocial behavior, including empathy, social norms, religious beliefs, self-efficacy, and the quality of interpersonal relationships. In educational contexts, character education strategies, empathy development, and the implementation of collaborative learning approaches have proven effective in cultivating students’ prosocial tendencies. These findings reinforce the view that prosocial behavior is not instinctive but develops through social learning and the internalization of cultural values, which are reinforced by the surrounding environment. Accordingly, educational institutions and community structures play a pivotal role in shaping individuals with a strong orientation toward social concern.